Historical dialectical materialism in the learning of the elderly person in the promotion of health care (Research, Society and Development, 2020)
To describe the theoretical and methodological construction of historical and dialectical materialism in the learning of the elderly in the promotion of health care. This research is an integral part of the study, approved by the Research Ethics Committee of the Pontifical Catholic University of Rio Grande do Sul PUCRS with registration number 2.202.003, entitled: “The teaching and learning processes: the educational dimension in the promotion Health Care of the Elderly ”and developed on the basis of dialectical historical materialism. The historical and dialectical materialism allows us to identify when the health professional learns to know the learning needs of the elderly, so that they can teach them the basic care of daily life according to their environment. In describing the methodological theoretical construction of historical and dialectical materialism in the learning of the elderly in the promotion of health care, the study entitled “The teaching and learning processes: the educational dimension in the promotion of health care for the elderly”, was It is possible to build knowledge about the changes that accompany the aging process from the psychological, sociological and psycho-behavioral point of view, as well as to study the nature and the modalities of adaptation of the individual in their transformations in the social context.